Driving-related cognitive skills during antidepressant transcranial direct current stimulation: results in a subsample from the DepressionDC trial - Burkhardt, Gerrit; Goerigk, Stephan; Dechantsreiter, Esther; Bulubas, Lucia; Soldini, Aldo; Zwanzger, Peter; Diemer, Julia; Padberg, Frank; Brunnauer, Alexander; Kumpf, Ulrike (Frontiers in Psychiatry, 2023)
Therapeutic transcranial direct current stimulation (tDCS) is a well-tolerated neuromodulatory intervention. However, there are currently no data on its impact on driving skills. Therefore, we conducted a validated assessment of driving-related cognitive skills in participants of the DepressionDC trial, a multicenter, randomized-controlled trial investigating the antidepressant effects of 6-week prefrontal tDCS in patients with major depressive disorder (MDD). Twenty-one patients (12 women, active tDCS, n=11; sham, n = 10) underwent an assessment of driving-related cognitive skills before and after the intervention. Using a Bayesian analysis approach, we found no group differences between active tDCS and sham tDCS in the pre-post treatment changes for visual perception (estimated median difference: 3.41 [-3.17, 10.55 89%-CI], BF01: 2.1), stress tolerance (estimated median difference: 0.77 [-2.40, 4.15 89%-CI], BF01: 1.6), and reaction time (estimated median difference: 2.06 [-12.33, 16.83 89%-CI], BF01: 6.5). Our results indicate that repeated 2 This is a provisional file, not the final typeset article sessions of a conventional bifrontal tDCS protocol do not negatively impact driving-related cognitive skills in patients with MDD.